Shear bond strength of stainless steel brackets bonded to porcelain surface treated with 1.23% acidulated phosphate fluoride gel compared to hydro fluoric acid with silane coupling agent (In vitro comparative study) - Tariq M Al-Najjar; Fakhri A Ali (College of Dentistry/ University of Baghdad, 2014)
Background: With the increasing demands for adult orthodontics, a growing need arises to bond attachments to porcelain surfaces. Optimal adhesion to porcelain surface should allow orthodontic treatment without bond failure but not jeopardize porcelain integrity after debonding.The present study was carried out to compare the shear bond strength of metal bracket bonded to porcelain surface prepared by two mechanical treatments and by using different etching systems (Hydrofluoric acid 9% and acidulated phosphate fluoride 1.23%). Materials and Methods: The samples were comprised of 60 models (28mm *15mm*28mm) of metal fused to porcelain (feldspathic porcelain). They were divided as the following: group I (control): the porcelain surface left untreated and glazed, group II (Diamond bur group): the porcelain surface was treated with fine diamond bur at speed of 350000 rpm for 20 seconds, group III (Red stone bur): the porcelain surface was treated with coarse red stone bur at speed of 8500 rpm for 20 seconds. Each group consists of 20 samples, then each group subdivided into two subgroups; one treated with acidulated phosphate fluoride 1.23% and the other subgroup treated with Hydrofluoric acid 9 % with silane coupling agent. Results: The result of this study revealed that there was very high significant difference among all tested groups and the highest shear bond strength was for diamond bur group with HFA and Silane (8.67 MPa), the 2nd highest strength was for control group with HFA and Silane (7.52 MPa), the 3rd was (7.38 MPa) in red stone bur with HFA and Silane, the least shear bond strength values were obtained for subgroups treated with acidulated phosphate fluoride gel 1.23%. Conclusions: The most reliable procedure for bonding orthodontic brackets to the porcelain surfaces is through the surface treatment combinations of mechanical roughening by using diamond bur, 9% Hydrofluoric acid and Silane coupling agent application.